Evidentiary Standards in Islamic Procedural Law: Reconciling Classical Fiqh with Modern Judicial Practices - Ulil Albab; Ika Verliana Septiani (Jurnal Hukum Replik, 2026)
This study examines the transformation of evidentiary standards in Islamic procedural law by analyzing the relationship between classical fiqh doctrines and contemporary judicial practices. Classical Islamic jurisprudence developed a structured evidentiary system consisting of testimony, confession, oath, and circumstantial indication, each grounded in principles of justice, reliability, and moral accountability. These standards reflect an epistemological approach that prioritizes predominant probability in establishing legal truth. However, the rapid development of modern legal systems, particularly through the use of documentary, forensic, and digital evidence, has created new challenges that require a reexamination of how evidence is defined and evaluated within Islamic courts. Using a doctrinal and conceptual approach, this study explores the extent to which classical evidentiary principles can accommodate contemporary forms of proof. The findings indicate that Islamic evidentiary law is inherently flexible and capable of adaptation through interpretive mechanisms rooted in its own legal tradition. In particular, the concept of circumstantial evidence provides a critical bridge for integrating modern evidentiary practices without undermining the normative foundations of Islamic law. This research proposes a reconciliatory framework that emphasizes the continuity of core legal values alongside methodological adaptation, supported by judicial reasoning and procedural standardization. The study concludes that the perceived tension between classical fiqh and modern judicial practice is not a structural incompatibility, but rather a reflection of the need for contextual reinterpretation. By articulating an integrated evidentiary paradigm, this research contributes to strengthening the relevance and functionality of Islamic procedural law in contemporary legal systems, particularly in jurisdictions that operate within pluralistic legal frameworks. The findings offer both theoretical and practical implications for the development of evidentiary standards that are consistent with the objectives of Islamic law while responsive to modern legal challenges.Keywords: Islamic procedural law, evidentiary standards, classical fiqh, modern judicial practices, legal reconciliation